The association of salivary alpha-amylase, heart rate variability, and psychological stress on objectively measured sleep behaviors among college students - Suh Minhee (Sciendo, 2022)
This study aimed to evaluate sleep behaviors among college students, to assess salivary alpha-amylase (sAA) and heart rate variability (HRV) in association with stress, and to investigate sleep-related factors including sAA, HRV, and stress among them.